Creation of a database to assess effects of omega-3, omega-6 and total polyunsaturated fats on health: methodology for a set of systematic reviews. Issue 5 (24th May 2019) - Hooper, Lee; Abdelhamid, Asmaa; Brainard, Julii; Deane, Katherine H O; Song, Fujian
Abstract : Objective: To create a database of long-term randomised controlled trials (RCTs) comparing higher with lower omega-3, omega-6 or total polyunsaturated fatty acid (PUFA), regardless of reported outcomes, and to develop methods to assess effects of increasing omega-6, alpha-linolenic acid (ALA), long-chain omega-3 (LCn3) and total PUFA on health outcomes. Design: Systematic review search, methodology and meta-analyses. Data sources: Medline, Embase, CENTRAL, WHO International Clinical Trials Registry Platform, Clinicaltrials.gov and trials in relevant systematic reviews. Eligibility criteria: RCTs of ≥24 weeks' duration assessing effects of increasing ALA, LCn3, omega-6 or total PUFAs, regardless of outcomes reported. Data synthesis: Methods included random-effects meta-analyses and sensitivity analyses. Funnel plots were examined, and subgrouping assessed effects of intervention type, replacement, baseline diabetes risk and use of diabetic medications, trial duration and dose. Quality of evidence was assessed using Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results: Electronic searches generated 37 810 hits, de-duplicated to 19 772 titles and abstracts. We assessed 2155 full-text papers, conference abstracts and trials registry entries independently in duplicate. Included studies were grouped into 363 RCTs comparing higher with lower omega-3, omega-6 and/or total PUFA intake of at least 6 months' duration—the Database. Of these 363 included RCTs, 216 RCTs were included in at least one of our reviews of health outcomes, data extracted and risk of bias assessed in duplicate. Ninety five RCTs were included in the Database but not included in our current reviews. Of these 311 completed trials, 27 altered ALA intake, 221 altered LCn3 intake and 16 trials altered omega-3 intake without specifying whether ALA or LCn3. Forty one trials altered omega-6 and 59 total PUFA.The remaining 52 trials are ongoing though 13 (25%) appear to be outstanding, or constitute missing data. Conclusions: This extensive database of trials is available to allow assessment of further health outcomes.